Polish and Slovene Noun Derivatives with the Meaning ‘hierarchy’ (Selected Issues of Description) - Kowalski, Paweł (Slavic Languages Today: Categories, Structures and Processes, 2021)
The aim of this article is to characterise the word-formation category of “hierarchy” and to compare Polish and Slovene noun derivatives expressing the common meanings of this category. The starting point is therefore the word-formation category which constitutes the implementation of the general semantic category “hierarchy”. The study focuses on selected issues of grammatisation of this semantic field in Polish and Slovene.